Preventing School Dropout in Maluku: Synergy Between Family, School, and Customary Values - Weridity, Mince Indira Ghandi; Manuputty, Feky (Baileo: Jurnal Sosial Humaniora, 2024)
This article aims to examine the collaboration between family, school, and customary values in efforts to prevent school dropouts in Maluku. This research uses a qualitative approach with a case study method on several schools in the Maluku region. Data were obtained through in-depth interviews, observation, and documentation related to the interaction between families, schools, and indigenous communities. The results of the study show that families play a crucial role in addressing the issue of school dropouts through effective communication and motivation for children to continue their education to higher levels. On the other hand, schools contribute by building strong relationships with parents, providing counseling guidance, identifying at-risk students, and offering remedial programs and scholarships. Maluku’s customary values, such as masohi, pela, and the philosophy of Potong di Kuku, Rasa di Daging, make significant contributions in emphasizing solidarity and togetherness, which function as social mechanisms to maintain the continuity of education. These findings affirm the importance of synergy between family, school, and customary values in creating an inclusive and sustainable educational ecosystem. The novelty of this research lies in revealing how local customary values can be effectively integrated into educational policies to prevent school dropouts. The recommendation of this study is the importance of strengthening the role of families, schools, and indigenous communities in shaping educational policies based on local wisdom to support social and humanitarian development.